PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA DI WILAYAH HUKUM POLRESTA PEKANBARU - Anny Yuserlina; Failin Failin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Violence, especially domestic violence (KDRT), is a violation of human rights. Human rights are a very sensitive matter in human life. Almost all countries have their own regulations to protect human rights, but they are often overlooked, especially regarding gender differences between men and women. Women are often considered inferior to men, so cases of domestic violence often arise. Violence in any form carried out for any reason is a form of crime that cannot be justified, therefore, no matter how small the violence committed, it can be reported as a criminal act that can be processed by law.Keywods: Legal Protection, Victims, Domestic Violence